Incidence and Epidemiology of Foot and Ankle Injuries in Elite Collegiate Athletes. (February 2017) - Hunt, Kenneth J.; Hurwit, Daniel; Robell, Kevin; Gatewood, Corey; Botser, Itamar B.; Matheson, Gordon
Background: Foot and ankle injuries are increasing in competitive professional and collegiate athletics. Many of these injuries result in considerable missed time from sports and often require surgical intervention. To develop and implement effective practice participation strategies, return-to-play protocols, and injury prevention programs, an understanding of injury trends and epidemiology is vital. Purpose: This study aimed to evaluate the incidence of foot and ankle injuries in elite athletes participating in 37 sports at a single National Collegiate Athletics Association (NCAA) Division 1 institution. Study Design: Descriptive epidemiological study. Methods: We evaluated the injury records of all varsity sports at a single NCAA Division 1 athletics program, including 1076 athletes participating in 37 sports. Detailed injury data were prospectively collected in a secure electronic database over a 2-year period. We reviewed the database for all foot/ankle injuries. Inclusion criteria were any foot/ankle injury that was sustained during an NCAA-sanctioned event and subsequently received medical treatment. Independent variables included athlete and injury demographics, missed days, physician visits, imaging results, and whether the injury required surgery. Injury incidence, relative frequency distributions, and sample proportions were dependent metrics for this investigation. Results: During the study period, a total of 3861 total musculoskeletal injuries were recorded. There were 1035 foot/ankle injuries (27%). Of all foot/ankle injuries, 21% (218 of 1035) caused the athlete to miss at least 1 day of participation, with an average of 12.3 days of time loss from sport. Furthermore, 27% of athletes with foot/ankle injuries were referred for office evaluation by a physician, and 84% of these required radiologic imaging. The overall injury incidence rate was 3.80 per 1000 athlete-exposures (AEs). The 4 sports with the highest incidence rate (>75th percentile) were women's gymnastics, women's cross-country, women's soccer, and men's cross country. The most frequently occurring foot/ankle injuries were ankle ligament injuries, tendinopathies or fasciopathies, and bone stress injuries. Conclusion: The prevalence of foot/ankle injury in a large NCAA Division 1 athletics program was 27% of total musculoskeletal injuries over a 2-year period, with 21% of these injuries resulting in missed time. There were significantly higher foot and ankle injury incidence rates and more missed time in female athletes and women's sports.